Synthesis and Host–Guest Properties of Acyclic Pillar[n]naphthalenes - Jia, Yuanyin; Dong, Ming; Wang, Bin; Li, Chunju (Frontiers in Chemistry, 2019)
Here we report a new class of synthetic receptors, acyclic pillar[n]naphthalene (n = 2−4, Dimer, Trimer, and Tetramer) oligomers, which are made up of 2,3-diethoxynaphthalene units linked by methylene bridges at the 1- and 4-positions. They can be synthesized through a one-step condensation of 2,3-diethoxynaphthalene monomer and paraformaldehyde in the presence of BF3⸱(Et)2O catalyst. The crystal structure of Tetramer has an interesting pseudo-cycle shaped structure in the solid state. Their complexation behaviors towards several organic ammonium cations (1+−15+) and electron–deficient neutral guests (16−17), were examined by means of 1H NMR spectroscopy. Tetramer shows good host-guest properties towards the ammonium guests, giving association constants (Ka) in the magnitude of 102−104 M−1, which are comparable with those for some macrocyclic hosts.